Clinicopathologic features of dual chronic hepatitis B and C infection: A comparison with single hepatitis B, C and delta infections - (:unkn) unknown (ELSEVIER ESPANA, 2008)
There is controversial data in the literature about the characteristics or features of dual hepatitis B and C infection. Several studies have reported that the dual infection has a more severe histological picture; faster progression leading to cirrhosis and a higher risk for hepatocellular carcinoma compared with the single infections. These findings have not yet been supported. We assessed the patients with dual hepatitis B and C infection-with respect to their different features in our country. Method: the chronic hepatitis patients of our clinics were tested, and both HBsAg and anti-HCV positive patients with chronic hepatitis were enrolled to the study. All patients were tested for the biochemical parameters and the presence of HBV-DNA and HCV-RNA. Results: Of the 1950 patients, 51 (2.6%) were both HBsAg and anti-HCV positive and 67 were ant-idelta positive. Patients were followed up for 5.4 +/- 2.1 years. Of the 51 dual hepatitis patients, 6 had no HBV-DNA and HCV-RNA detectable by PCR, 36 were only HCV-RNA positive, 9 were only HBV-DNA positive and 3 were both HBV-DNA and HCV-RNA positive. Dominant infection in 3/4 of the patients was hepatitis C. Clinical and histological properties of the cases with dual Hepatitis B and C infection showed no significant differences compared to the single infections. In conclusion, regarding the prognosis, no significant differences were found between such dual and single infections. Dual infection with hepatitis B virus and delta virus is a significantly more severe condition than the dual infection with hepatitis B and C viruses.
Keywords: chronic Hepatitis B and C; hepatitis delta virus; liver cirrhosis; hepatocellular carcinoma; VIRUS-INFECTION; VIROLOGICAL PROFILES; VIRAL-HEPATITIS; COINFECTION; FULMINANT; AREA; HCV